Therapeutic benefits in grid irradiation on Tomotherapy for bulky, radiation-resistant tumors. (3rd August 2017) - Narayanasamy, Ganesh; Zhang, Xin; Meigooni, Ali; Paudel, Nava; Morrill, Steven; Maraboyina, Sanjay; Peacock, Loverd; Penagaricano, Jose
Abstract: Introduction: Spatially fractionated radiation therapy (SFRT or grid therapy) has proven to be effective in management of bulky tumors. The aim of this project is to study the therapeutic ratio (TR) of helical Tomotherapy (HT)-based grid therapy using linear–quadratic cell survival model. Material and Methods: HT-based grid (or HT-GRID) plan was generated using a patient-specific virtual grid pattern of high-dose cylindrical regions using MLCs. TR was defined as the ratio of normal tissue surviving fraction (SF) under HT-GRID irradiation to an open debulking field of an equivalent dose that result in the same tumor cell SF. TR was estimated from DVH data on ten HT-GRID patient plans with deep seated, bulky tumor. Dependence of the TR values on radiosensitivity of the tumor cells and prescription dose was analyzed. Results: The mean ± standard deviation (SD) of TR was 4.0 ± 0.7 (range: 3.1–5.5) for the 10 patients with single fraction maximum dose of 20 Gy to GTV assuming a tumor cell SF at 2 Gy (SF2t ) value of 0·5. In addition, the mean ± SD of TR values for SF2t values of 0.3 and 0.7 were found to be 1 ± 0.1 and 18.0 ± 5.1, respectively. Reducing the prescription dose to 15 and 10 Gy lowered the respective TR values to 2.0 ± 0.2 and 1.2 ± 0.04 for a SF2t value of 0.5. Conclusion: HT-GRID therapy demonstrates a significant therapeutic advantage over uniform dose from an open field irradiation for the same tumor cell kill. TR increases with the radioresistance of the tumor cells and with prescription dose.